HUBUNGAN FAKTOR SOSIAL EKONOMI DAN ASUPAN ZAT GIZI TERHADAP STATUS GIZI LANSIA DI WILAYAH KERJA PUSKESMAS SUDIANG RAYA KOTAMADYA MAKASSAR - Pateda, Sri Manovita (Jurnal Entropi, 2009)
Health and functional status of the old is determined by the resultant of physic, psychology, and economic social factors of that human. Those factors role are not same each other. Therefore, it has to be improved together in total patient care way. At the olds, energy needed that down because of activity, will cause the needed of choosing and processing. Thus, it can obtain a health foodstuff, because lack or over of energy or nutrient of food can give unexpected effect. Result of data analyses is obtained and concluded that there is no relationship between variables of economy social factor and nutrient feed towards the olds nutrient status in working field of Local Government Clinic of Sudiang Raya.